Sex differences in the relationship between parathyroid hormone and uric acid in osteoporotic fracture patients: insights from a retrospective cross-sectional study - Zhu, Cheng-bai; Zhou, Peng; Lu, Ke; Li, Chong; Wei, Yin-lin; Jin, Jian; Hu, Wen-bin; Gao, Yi-jun (Frontiers in Endocrinology, 2025)
BackgroundOsteoporosis (OP) is characterized by decreased bone mineral density and increased fracture risk, particularly in older adults. The relationship between parathyroid hormone (PTH) and uric acid (UA) levels among osteoporotic fracture (OPF) patients remains unclear. This study aimed to investigate the association between PTH and UA in a large OPF patient cohort.MethodsIn this retrospective cross-sectional study, clinical data from 1,730 OPF patients admitted to Kunshan Hospital of Jiangsu University between January 2017 and August 2023 were analyzed. Baseline PTH and UA levels were measured, and analyses adjusted for age, sex, body mass index (BMI), and other clinical parameters. Multivariable logistic regression, smooth curve fitting, and threshold analyses were conducted.ResultsAfter stratifying by gender and adjusting for covariates, regression analysis revealed a significant positive association between PTH and UA in males, with each unit increase in PTH corresponding to a 2.19 µmol/L rise in UA (β=2.19, 95% CI: 1.27–3.12, p<0.01). Similarly, females exhibited a positive association, with each unit increase in PTH associated with a 0.88 µmol/L increase in UA (β=0.88, 95% CI: 0.35–1.40, p<0.01). Additionally, a nonlinear relationship was identified in female patients, with a UA inflection point at 26.14 µmol/L.ConclusionA significant positive correlation between PTH and UA levels exists among OPF patients, with males exhibiting a linear and females a nonlinear relationship. These findings highlight the importance of gender-specific personalized management strategies in clinical practice.